Case Report: Late simultaneous metastasis of renal clear cell carcinoma to the ampulla and breast - Dai, Guofeng; Li, Shuya; Sun, Lei; Wang, Gangpu (Frontiers in Oncology, 2025)
We present the case of a 67-year-old female who developed simultaneous metastases to the ampulla of Vater and the breast. Her medical history is significant for a radical nephrectomy performed twenty-one years prior for renal cell carcinoma (RCC). The patient was referred for evaluation due to the development of progressive jaundice, fatigue, and weight loss. A computed tomography (CT) scan of the abdomen revealed a 40 mm nodule located at the ampulla of Vater, accompanied by dilatation of the bile duct, indicative of obstructive jaundice. Additionally, ultrasonography identified a mass approximately 20 mm in size in the lateral portion of the left breast. The patient underwent a pancreatoduodenectomy to address the ampullary mass and a lumpectomy for the breast lesion. Histological examination of the resected specimens confirmed the diagnosis of metastases from RCC in both the ampulla of Vater and the breast.